Sinergi Program Keluarga Berencana (KB) Dan Dinas Sosial Kota Malang: Mewujudkan Kesejahteraan Keluarga Pra-Sejahtera - Aqny Ghaida Velly Siti (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This article discusses the synergy between the Family Planning (KB) Program and the Malang City Social Service in an effort to improve the welfare of underprivileged families. By emphasizing the individual's right to independently regulate their reproductive life, this article presents an analysis of the regulations underlying the implementation of the program, including the Regulation of the Head of BKKBN and related laws and regulations. The main focus of this study is the challenges faced by underprivileged families, such as low education, limited access to health services, and unstable economic conditions. Through a cross-sectoral approach, interventions carried out by the KB program and the Social Service are expected to improve the quality of life of the community. Through the literature review method, the author analyzes various sources to understand the impact of public policy on families. The results of the study show that the collaboration between the two programs not only focuses on controlling population numbers, but also on improving the quality of life through education and health services. Through various activities, such as counseling, data collection, and mobile services, both institutions strive to reach families in need. The evaluation results show an increase in awareness and access to services, although challenges in coordination and resources still exist.